2013
DOI: 10.1371/journal.pone.0074437
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 2 Overexpression in Tumor Stroma Identifies Invasive Ductal Carcinomas of Breast at High Risk of Recurrence

Abstract: IntroductionMolecular markers for predicting breast cancer patients at high risk of recurrence are urgently needed for more effective disease management. The impact of alterations in extracellular matrix components on tumor aggressiveness is under intense investigation. Overexpression of Transglutaminase 2 (TG2), a multifunctional enzyme, in cancer cells impacts epithelial mesenchymal transition, growth, invasion and interactions with tumor microenvironment. The objective of our study is to determine the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 44 publications
(59 reference statements)
1
28
0
1
Order By: Relevance
“…SPON2 and its translational product, Spondin-2, have been found to be up-regulated in many types of cancer [37][38][39], and its expression is a prognostic factor in prostate and colorectal cancer [40,41]. In breast cancer, expression of TGM2 in tumor stroma is an independent risk factor for breast cancer patients at high risk of recurrence [42]. In AML, TGM2 was found up-regulated particularly in relapsed patients and correlated with increased expression of numerous adhesion proteins and many apoptosis regulating proteins [43].…”
Section: Discussionmentioning
confidence: 99%
“…SPON2 and its translational product, Spondin-2, have been found to be up-regulated in many types of cancer [37][38][39], and its expression is a prognostic factor in prostate and colorectal cancer [40,41]. In breast cancer, expression of TGM2 in tumor stroma is an independent risk factor for breast cancer patients at high risk of recurrence [42]. In AML, TGM2 was found up-regulated particularly in relapsed patients and correlated with increased expression of numerous adhesion proteins and many apoptosis regulating proteins [43].…”
Section: Discussionmentioning
confidence: 99%
“…Assi et al (20) reported that patients with stromal TG2 accumulation had significantly decreased disease-free survival (DFS; mean DFS, 110 months) compared with patients with low TG2 expression (mean DFS, 130 months). On the basis of these observations, it may be hypothesized that high TG2 expression levels correlate with poor clinical outcome in patients with breast cancer, which leads to a decreased sensitivity to TXT chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CD73 is expressed not only on MSC but also on tumor cells and Treg cells, suggesting that the adenosine found within TME can be derived from different sources, to further amplify the strong inhibitory effect derived from a single cell type [13,14,15]. Transglutaminase (TG)-II can be used to selectively identify MSC in immunohistochemistry and cytofluorimetry [16,17,18,19,20,21,22,23]; however, it is also expressed on tumor cells undergoing EMT. TG-II is involved in several processes that can regulate tumor cell proliferation and apoptosis [16,17,18,19,20,21].…”
Section: Msc Phenotypic and Functional Features Relevant In The Inmentioning
confidence: 99%